High-strength corrosion-resistant TA24 titanium alloy and preparation method thereof

CN122707096BActive Publication Date: 2026-10-20BAOJI JUXINYUAN NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611170453.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-20
Estimated Expiration
2046-08-04

AI Technical Summary

Technical Problem

其中有机防护涂层长期使用易出现起皮脱落现象,脱落区域会造成氯离子等腐蚀介质局部聚集,进而导致基体发生点蚀与缝隙腐蚀;现有技术中,在钛合金表面磁控溅射α-氧化铝复合层,再进行微弧氧化制备α-氧化铝复合层;但是微弧氧化时间过长,易击穿铝保护层,造成钛合金基体局部氧化,同时α-氧化铝复合层因热应力产生贯穿裂纹等缺陷,故而影响钛合金的力学性能和耐腐蚀性

Benefits of technology

本发明采用Ti、Al-Cr双靶材共溅射制备Ti-Al-Cr合金前驱层,依靠Ti、Cr金属相形成稳定刚性支撑骨架,经脱Al造孔,可有效避免多孔结构坍塌,避免TA24基体外露,形成多孔Ti-Al-Cr层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a high-strength corrosion-resistant TA24 titanium alloy and a preparation method thereof, and relates to the technical field of TA24 titanium alloys. The preparation method comprises the following steps: taking Ti and Al-Cr as target materials, magnetron sputtering a Ti-Al-Cr alloy layer on the surface of the TA24 titanium alloy, de-alloying, forming a porous Ti-Al-Cr alloy layer, calcining in air, and obtaining a pre-prepared TA24 titanium alloy; placing the pre-prepared TA24 titanium alloy in an electrolyte, micro-arc oxidation, and forming a micro-arc oxidation layer; and taking aluminum / alpha-aluminum oxide as a composite target material, magnetron sputtering an alpha-aluminum oxide composite layer on the surface of the micro-arc oxidation layer, and heat treating, so as to obtain the high-strength corrosion-resistant TA24 titanium alloy. The high-strength corrosion-resistant TA24 titanium alloy prepared in the scheme has good mechanical properties and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of TA24 titanium alloy technology, specifically a high-strength, corrosion-resistant TA24 titanium alloy and its preparation method. Background Technology

[0002] TA24 titanium alloy, with its high specific strength and corrosion resistance, has been widely used in harsh service scenarios such as shipbuilding and marine engineering, petrochemicals, aviation auxiliary equipment, and thermal energy equipment. However, in complex marine environments, this alloy is still prone to stress corrosion cracking and biofouling, which significantly reduces the service life of equipment.

[0003] Currently, the industry mainly improves the corrosion resistance of TA24 titanium alloy through surface modification, with common processes including micro-arc oxidation, magnetron sputtering, and organic coating. However, organic protective coatings are prone to peeling and flaking with prolonged use, leading to localized accumulation of corrosive media such as chloride ions in the flaked areas, which in turn causes pitting and crevice corrosion in the substrate. Existing technology involves magnetron sputtering an α-alumina composite layer onto the titanium alloy surface, followed by micro-arc oxidation to prepare the α-alumina composite layer. However, excessively long micro-arc oxidation times can easily break through the aluminum protective layer, causing localized oxidation of the titanium alloy substrate. Simultaneously, the α-alumina composite layer develops defects such as through-cracks due to thermal stress, thus affecting the mechanical properties and corrosion resistance of the titanium alloy.

[0004] In summary, the preparation of a high-strength, corrosion-resistant TA24 titanium alloy is of great significance. Summary of the Invention

[0005] The purpose of this invention is to provide a high-strength, corrosion-resistant TA24 titanium alloy and its preparation method, so as to solve the problems mentioned in the background art.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a high-strength, corrosion-resistant TA24 titanium alloy includes the following steps: Step 1: Using Ti and Al-Cr as targets, a Ti-Al-Cr alloy layer is magnetron sputtered on the surface of TA24 titanium alloy. After dealloying, cleaning, and drying, a porous Ti-Al-Cr alloy layer is formed. The layer is then calcined in air to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Mix sodium silicate, sodium hexametaphosphate, potassium hydroxide, glycerol, α-alumina and nano silica to obtain an electrolyte; (2) Place the pre-made TA24 titanium alloy in the electrolyte and perform micro-arc oxidation to form a micro-arc oxide layer; (3) Use aluminum / α-alumina as a composite target to magnetron sputter an α-alumina composite layer on the surface of the micro-arc oxide layer, and heat treat to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0007] A more optimized process condition for the magnetron sputtering of the Ti-Al-Cr alloy layer is as follows: using Ti and Al-Cr as targets, with a Cr content of 30~40wt% in Al-Cr, and a vacuum degree of 2.0×10⁻⁶. -3 ~5.0×10 -3 Pa, argon flow rate of 30~60 sccm, sputtering power of Al-Cr of 0.75~1.75 kW, sputtering power of Ti of 1.75 kW.

[0008] A more optimized process condition for the magnetron sputtering of the α-alumina composite layer is as follows: using aluminum / α-alumina as the composite target, with an α-alumina content of 15-20 wt%, an argon flow rate of 30-60 sccm, an oxygen flow rate of 20-35 sccm, and a vacuum degree of 5.0 × 10⁻⁶. -4 ~2.0×10 -3 Pa, deposition temperature of 500~560℃, and RF power of 170~210W.

[0009] A more optimized process is as follows: magnetron sputtering a Ti-Al-Cr alloy layer on the surface of TA24 titanium alloy, placing it in liquid magnesium at 700~800℃ for dealloying for 8~15 minutes, cooling to room temperature, placing it in 3M nitric acid aqueous solution for dealloying for 20~40 minutes, washing, and vacuum drying.

[0010] A more optimized calcination process is as follows: temperature 300~500℃, time 30~70 minutes.

[0011] In a more optimized form, the electrolyte comprises the following components: 8-12 g / L sodium silicate, 3-5 g / L sodium hexametaphosphate, 1-3 g / L potassium hydroxide, 5-8 g / L glycerol, 1-5 g / L α-alumina, and 0.3-0.8 g / L nano-silica; wherein the α-alumina has a particle size of 10-50 nm, and the nano-silica has a particle size of 10-30 nm.

[0012] The optimized process conditions for micro-arc oxidation are: voltage of 380~550V, pulse frequency of 400~600Hz, duty cycle of 10~30%, temperature of 20~45℃, and stirring speed of 100~300r / min; the process conditions for heat treatment are: temperature of 300~500℃ and time of 1~2 hours.

[0013] In a more optimized configuration, the thickness of the Ti-Al-Cr alloy layer is 10~15μm; the thickness of the micro-arc oxidation layer is 4~6μm; and the thickness of the α-alumina composite layer is 8~12μm.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention uses Ti and Al-Cr dual-target co-sputtering to prepare a Ti-Al-Cr alloy precursor layer. The Ti and Cr metallic phases form a stable and rigid support framework. After Al removal and pore creation, the collapse of the porous structure can be effectively avoided, and the TA24 substrate can be prevented from being exposed, thus forming a porous Ti-Al-Cr layer.

[0015] After air calcination, a composite oxide phase of titanium dioxide, γ-alumina, and chromium oxide is generated in situ in the porous transition layer. Among them, chromium oxide has a similar crystal structure to α-alumina in the micro-arc oxidation system and has good interfacial compatibility. Titanium dioxide can effectively induce and promote the formation of α-alumina during the micro-arc oxidation process. γ-alumina synergistically improves the drawbacks of pure α-alumina coating, such as high brittleness and easy cracking, thereby effectively improving the overall mechanical strength and corrosion resistance of the coating.

[0016] Micro-arc oxidation is performed using an electrolyte containing nano-α-alumina and nano-silica to fill the interconnected pores within the porous composite oxide layer and effectively reduce internal cavity defects. Then, an outer α-alumina composite layer is prepared by magnetron sputtering using aluminum / α-alumina as a composite target, achieving surface sealing of pores. The multi-layer structure works synergistically to improve the overall mechanical strength and corrosion resistance of the titanium alloy. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1: A method for preparing a high-strength, corrosion-resistant TA24 titanium alloy, comprising the following steps: Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At a speed of Pa and an argon flow rate of 45 sccm, the sputtering power of Ti was 1.75 kW and the sputtering power of Al-Cr was 0.75 kW. Magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm. The layer was then placed in liquid magnesium at 800 °C for 8 minutes to de-alloy, cooled to room temperature, placed in 3M nitric acid aqueous solution, and de-alloyed at 22 °C for 30 minutes. The layer was then removed, cleaned, and vacuum dried to form a porous Ti-Al-Cr alloy layer. Finally, the layer was placed in an air atmosphere and calcined at 400 °C for 60 minutes to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and 0.3 g / L nano silica and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0019] The Al-Cr target material contains 30 wt% Cr; the particle size of α-alumina is 20 nm, and the particle size of nano-silica is 10 nm.

[0020] Example 2 is based on Example 1; the difference is that it involves dealloying in liquid magnesium for 10 minutes; the other operating steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At a speed of Pa and an argon flow rate of 45 sccm, the sputtering power of Ti was 1.75 kW and the sputtering power of Al-Cr was 0.75 kW. Magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm. The layer was then placed in liquid magnesium at 800 °C for dealloying for 10 minutes, cooled to room temperature, placed in 3M nitric acid aqueous solution, and dealloyed at 22 °C for 30 minutes. The layer was then removed, cleaned, and vacuum dried to form a porous Ti-Al-Cr alloy layer. Finally, the layer was placed in an air atmosphere and calcined at 400 °C for 60 minutes to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and 0.3 g / L nano silica and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0021] The Al-Cr target material contains 30 wt% Cr; the particle size of α-alumina is 20 nm, and the particle size of nano-silica is 10 nm.

[0022] Example 3 is based on Example 1; the difference is that it is de-alloyed in liquid magnesium for 15 minutes; the other operating steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At a pressure of Pa, argon flow rate of 45 sccm, sputtering power of Ti of 1.75 kW and sputtering power of Al-Cr of 0.75 kW, magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm. The layer was then placed in liquid magnesium at 800 °C for dealloying for 15 minutes, cooled to room temperature, placed in 3M nitric acid aqueous solution, and dealloyed at 22 °C for 30 minutes. After removal, cleaning, and vacuum drying, a porous Ti-Al-Cr alloy layer was formed. The layer was then placed in an air atmosphere and calcined at 400 °C for 60 minutes to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and 0.3 g / L nano silica and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0023] The Al-Cr target material contains 30 wt% Cr; the particle size of α-alumina is 20 nm, and the particle size of nano-silica is 10 nm.

[0024] Testing and inspection; (1) Mechanical property test: According to GB / T229-2020 standard, TA24 titanium alloy and the high-strength corrosion-resistant TA24 titanium alloy prepared in Examples 1 to 3 are unnotched specimens, the pendulum size is 2mm, and the impact toughness (J / cm) is tested at room temperature. 2 ); (2) Electrochemical performance testing: The TA24 titanium alloy and the high-strength corrosion-resistant TA24 titanium alloy prepared in Examples 1-3 were placed in seawater for 35 days to test their corrosion resistance, and the seawater was replaced after 48 hours. The TA24 titanium alloy and the high-strength corrosion-resistant TA24 titanium alloy prepared in Examples 1-3 were used as working electrodes. The working electrodes were first immersed in seawater for 30 seconds to reach a stable state. Ag / AgCl was used as the reference electrode, and platinum foil was used as the counter electrode. The test results are shown in Table 1.

[0025] Table 1

[0026] Conclusion: The longer the dealloying time, the larger the porosity and the more cavities are formed in the Ti-Al-Cr alloy layer, which leads to a decrease in corrosion resistance and mechanical properties; among Examples 1 to 3, Example 1 has better performance; the following comparison is based on Example 1.

[0027] Comparative Example 1 is based on Example 1; the difference is that a porous Ti-Al-Cr alloy layer was not introduced; the other operating steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At Pa, the argon flow rate was 45 sccm, the sputtering power of Ti was 1.75 kW, and the sputtering power of Al-Cr was 0.75 kW; magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm; thus, a prefabricated TA24 titanium alloy was obtained. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and 0.3 g / L nano silica and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0028] The Al-Cr target material contains 30 wt% Cr; the particle size of α-alumina is 20 nm, and the particle size of nano-silica is 10 nm.

[0029] Comparative Example 2 is based on Example 1; the difference is that the thickness of the Ti-Al-Cr alloy layer is 3.0 μm; the other operating steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At a pressure of Pa, argon flow rate of 45 sccm, sputtering power of Ti of 1.75 kW and sputtering power of Al-Cr of 0.75 kW, magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 3.0 μm. This layer was then placed in liquid magnesium at 800 °C for dealloying for 8 minutes, cooled to room temperature, placed in 3M nitric acid aqueous solution, and dealloyed at 22 °C for 30 minutes. After removal, cleaning, and vacuum drying, a porous Ti-Al-Cr alloy layer was formed. This layer was then placed in an air atmosphere and calcined at 400 °C for 60 minutes to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and 0.3 g / L nano silica and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0030] The Al-Cr target material contains 30 wt% Cr; the particle size of α-alumina is 20 nm, and the particle size of nano-silica is 10 nm.

[0031] Comparative Example 3 is based on Example 1; the difference is that no micro-arc oxidation layer was provided; the other operation steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At a speed of Pa and an argon flow rate of 45 sccm, the sputtering power of Ti was 1.75 kW and the sputtering power of Al-Cr was 0.75 kW. Magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm. The layer was then placed in liquid magnesium at 800 °C for 8 minutes to de-alloy, cooled to room temperature, placed in 3M nitric acid aqueous solution, and de-alloyed at 22 °C for 30 minutes. The layer was then removed, cleaned, and vacuum dried to form a porous Ti-Al-Cr alloy layer. Finally, the layer was placed in an air atmosphere and calcined at 400 °C for 60 minutes to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: Using aluminum / α-alumina as the composite target material, with an α-alumina content of 15 wt%, the argon flow rate is set to 45 sccm, the oxygen flow rate to 25 sccm, and the vacuum degree to 5.0 × 10⁻⁶. -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the prefabricated TA24 titanium alloy to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0032] The Al-Cr target material contains 30 wt% Cr.

[0033] Comparative Example 4 is based on Example 1; the difference is that calcination was not performed; the other operating steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3 At a sputtering power of 45 sccm, argon flow rate was 45 kW, Ti sputtering power was 1.75 kW, and Al-Cr sputtering power was 0.75 kW. Magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm. This layer was then placed in liquid magnesium at 800 °C for dealloying for 8 minutes, cooled to room temperature, and placed in a 3M nitric acid aqueous solution for dealloying at 22 °C for 30 minutes. After removal, cleaning, and vacuum drying, a porous Ti-Al-Cr alloy layer was formed, resulting in a pre-fabricated TA24 titanium alloy. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and 0.3 g / L nano silica and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0034] The Al-Cr target material contains 30 wt% Cr; the particle size of α-alumina is 20 nm, and the particle size of nano-silica is 10 nm.

[0035] Comparative Example 5 is based on Example 1; the difference is that no nano-silica was added; the other operating steps are the same. Step 1: Using Ti and Al-Cr as dual targets, set the vacuum level to 5.0 × 10⁻⁶. -3At a speed of Pa and an argon flow rate of 45 sccm, the sputtering power of Ti was 1.75 kW and the sputtering power of Al-Cr was 0.75 kW. Magnetron sputtering was performed on the surface of TA24 titanium alloy to obtain a Ti-Al-Cr alloy layer with a thickness of 12.3 μm. The layer was then placed in liquid magnesium at 800 °C for 8 minutes to de-alloy, cooled to room temperature, placed in 3M nitric acid aqueous solution, and de-alloyed at 22 °C for 30 minutes. The layer was then removed, cleaned, and vacuum dried to form a porous Ti-Al-Cr alloy layer. Finally, the layer was placed in an air atmosphere and calcined at 400 °C for 60 minutes to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Dissolve 8 g / L sodium silicate, 4 g / L sodium hexametaphosphate, 2 g / L potassium hydroxide, and 6 g / L glycerol in deionized water by stirring. Add 2 g / L α-alumina and disperse evenly to obtain an electrolyte. Place the pre-made TA24 titanium alloy in the electrolyte for micro-arc oxidation. Set the voltage to 380V, the pulse frequency to 600Hz, the duty cycle to 20%, the temperature to 25℃, and the stirring speed to 200r / min to form a micro-arc oxidation layer with a thickness of 5.0μm. (2) Use aluminum / α-alumina as the composite target material. The content of α-alumina is 15wt%. Set the argon flow rate to 45sccm, the oxygen flow rate to 25sccm, and the vacuum degree to 5.0×10 -4 Pa, RF power is 185W; magnetron sputtering is performed on the surface of the micro-arc oxide layer to form an α-alumina composite layer with a thickness of 8.5μm; (3) it is placed in a nitrogen atmosphere and heat-treated at 450℃ for 1 hour to obtain a high-strength corrosion-resistant TA24 titanium alloy.

[0036] The Al-Cr target material contains 30 wt% Cr and has a particle size of 20 nm.

[0037] Testing: The high-strength, corrosion-resistant TA24 titanium alloys prepared in Comparative Examples 1-5 were tested for impact toughness (J / cm) according to the testing method in Example 1. 2 ), corrosion current density (A·cm) -2 The test results are shown in Table 2.

[0038] Table 2

[0039] Conclusion: Comparative Example 1 is based on Example 1; the difference is that a porous Ti-Al-Cr alloy layer was not introduced. Although the dense, non-porous Ti-Al-Cr layer provides the best toughness, the lack of "anchor points" in the porous structure leads to poor adhesion between the surface coating (micro-arc oxidation layer + sputtered layer) and the substrate. Microcracks are generated at the interface due to spark discharge from micro-arc oxidation, and corrosive media can easily penetrate along the cracks, thus significantly reducing corrosion resistance. Comparative Example 2 is based on Example 1; the difference is that the thickness of the Ti-Al-Cr alloy layer is 3.0 μm. The reduced thickness of the Ti-Al-Cr alloy layer causes cavities not only to appear in the Ti-Al-Cr alloy layer during dealloying, but also slight pores to appear on the surface of the TA24 titanium alloy. This results in pores between the Ti-Al-Cr alloy layer and the TA24 titanium alloy, thus leading to poor interlayer adhesion, increased stress concentration points, and decreased impact toughness. Comparative Example 3 is based on Example 1; the difference is that no micro-arc oxide layer is provided; the micro-arc oxide layer can fill the pores generated inside the porous composite oxide layer, while the subsequent magnetron sputtering cannot fill the internal pores, but only fills the surface pores, thus leading to a decrease in performance.

[0040] Comparative Example 4 is based on Example 1; the difference is that calcination was not performed. Without calcination, stable oxides such as γ-Al2O3 and TiO2 cannot be generated, and they still exist in metallic or amorphous forms, resulting in insufficient stability and structural density, thus leading to a decrease in performance. Comparative Example 5 is based on Example 1; the difference is that nano-silica was not added. Nano-silica usually refines grains and can fill pores and toughen during micro-arc oxidation. The absence of nano-silica in Comparative Example 5 leads to a decrease in performance.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a high-strength, corrosion-resistant TA24 titanium alloy, characterized in that: Includes the following steps: Step 1: Using Ti and Al-Cr as targets, a Ti-Al-Cr alloy layer is magnetron sputtered on the surface of TA24 titanium alloy. After dealloying, cleaning, and drying, a porous Ti-Al-Cr alloy layer is formed. The layer is then calcined in air to form a porous composite oxide layer, thus obtaining the pre-fabricated TA24 titanium alloy. Step 2: (1) Mix sodium silicate, sodium hexametaphosphate, potassium hydroxide, glycerol, α-alumina and nano silica to obtain an electrolyte; (2) The pre-made TA24 titanium alloy is placed in the electrolyte and micro-arc oxidation is performed to form a micro-arc oxidation layer; (3) Using aluminum / α-alumina as a composite target, an α-alumina composite layer is magnetron sputtered on the surface of the micro-arc oxide layer and then heat-treated to obtain a high-strength corrosion-resistant TA24 titanium alloy. The dealloying process conditions are as follows: magnetron sputtering of a Ti-Al-Cr alloy layer on the surface of TA24 titanium alloy, dealloying in liquid magnesium at 700~800℃ for 8~15 minutes, cooling to room temperature, dealloying in 3M nitric acid aqueous solution for 20~40 minutes, washing, and vacuum drying. The thickness of the Ti-Al-Cr alloy layer is 10~15μm.

2. The method for preparing a high-strength, corrosion-resistant TA24 titanium alloy according to claim 1, characterized in that: The process conditions for magnetron sputtering the Ti-Al-Cr alloy layer are as follows: Ti and Al-Cr are used as targets, the Cr content in Al-Cr is 30~40wt%, and the vacuum degree is 2.0×10⁻⁶. -3 ~5.0×10 -3 Pa, argon flow rate of 30~60 sccm, sputtering power of Al-Cr of 0.75~1.75 kW, sputtering power of Ti of 1.75 kW.

3. The method for preparing a high-strength, corrosion-resistant TA24 titanium alloy according to claim 1, characterized in that: The process conditions for the magnetron sputtering of the α-alumina composite layer are as follows: aluminum / α-alumina is used as the composite target material, the α-alumina content is 15~20wt%, the argon flow rate is 30~60sccm, the oxygen flow rate is 20~35sccm, and the vacuum degree is 5.0×10⁻⁶. -4 ~2.0×10 -3 Pa, deposition temperature of 500~560℃, and RF power of 170~210W.

4. The method for preparing a high-strength, corrosion-resistant TA24 titanium alloy according to claim 1, characterized in that: The calcination process conditions are: temperature 300~500℃, time 30~70 minutes.

5. The method for preparing a high-strength, corrosion-resistant TA24 titanium alloy according to claim 1, characterized in that: The raw materials for the electrolyte include the following components: The mixture contains 8-12 g / L sodium silicate, 3-5 g / L sodium hexametaphosphate, 1-3 g / L potassium hydroxide, 5-8 g / L glycerol, 1-5 g / L α-alumina, and 0.3-0.8 g / L nano silica; wherein the α-alumina has a particle size of 10-50 nm and the nano silica has a particle size of 10-30 nm.

6. The method for preparing a high-strength, corrosion-resistant TA24 titanium alloy according to claim 1, characterized in that: The micro-arc oxidation process conditions are: voltage 380~550V, pulse frequency 400~600Hz, duty cycle 10~30%, temperature 20~45℃, and stirring speed 100~300r / min; the heat treatment process conditions are: temperature 300~500℃, and time 1~2 hours.

7. The method for preparing a high-strength, corrosion-resistant TA24 titanium alloy according to claim 1, characterized in that: The thickness of the micro-arc oxidation layer is 4~6μm; the thickness of the α-alumina composite layer is 8~12μm.

8. The high-strength corrosion-resistant TA24 titanium alloy prepared by the method of preparing a high-strength corrosion-resistant TA24 titanium alloy according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for making housing and housing made by same

    CN101722778A

  • Surface recombination processing method for magnesium alloy microwave assembly cover plate

    CN104195569A